The zero-leverage phenomenon in European listed firms: A financing decision or an imposition of the financial market? - Morais, Flávio (2021)
This article provides empirical evidence on the zero-leverage phenomenon for a sample of European listed firms for the period 1995–2016. It is shown that there are two types of firms with zero leverage: the financially constrained firms that face obstacles in obtaining external finance, as predicted by the financial constraints hypothesis; and the financially unconstrained firms that maintain zero leverage as a consequence of a financing decision, which supports the financial flexibility hypothesis. The zero-leverage phenomenon is also influenced by the financial system that prevails in each country, being boosted (inhibited) in market-based (bank-based) financial systems, and by the country’s macroeconomic conditions, with the recent financial and sovereign debt crises increasing the propensity for zero leverage in market-based countries. We also find that the financial flexibility hypothesis seems to be more important in market-based systems and that the financial constraints approach did not gain importance during the crisis period. Our results are robust to the use of alternative measures of debt conservatism, explanatory variables, and econometric methods and maintain their validity when we allow for endogeneity in firm size and dividend payments.